A multimodal analysis of fallacies in Malaysian and Singaporean anti-smoking advertisement / Nurul Afiqah Laili - Nurul Afiqah , Laili (2019)
This multimodal study analysed anti-smoking print advertisements from Malaysia and Singapore’s anti-smoking campaigns using a combination of frameworks and approaches adapted from Van Leeuwen’s visual representation of social actors’ framework (2008), Kress and Van Leeuwen’s composition of images framework (2006[1996]) and McCandless’s (2012) classification of fallacies. Six anti-smoking print advertisements, three from each country were chosen as the data for the study. Through the data, the researcher aimed to identify the visual and textual realisation of fallacies as well as to compare the findings of the analysis obtained from each country. The outcomes of the analysis show the fallacies in the Malaysian and Singaporean anti-smoking advertisements being realised differently as the Malaysian fallacies were realised through both text and images whereas the Singaporean fallacies were mostly realised through text. Additionally, the fallacies utilised in the Singaporean advertisements were presented in a more positive manner compared to the fallacies in the Malaysian advertisements which led to the success of their anti-smoking campaign. The findings of this study will aid in the studies of various fields of research related to language, advertising and society.